Analysis of Maternal Death Based on Cycle Threshold Polymerase Chain Reaction Values in Pregnant Women Confirmed with COVID-19 - Aditia, Arianda; Utama, Winda Trijayanthi (Jurnal Penelitian Perawat Profesional, 2025)
COVID-19 is an infectious disease caused by SARS-CoV-2. COVID-19 infect all groups, including pregnant women, resulting in a high positive rate pregnant women. COVID-19 diagnosis process can be supported by RT-PCR test. The RT-PCR test there is a CT-Value which is used to see the viral load which can affect the severity of COVID-19, including pregnant women who experience physiological changes in the body that can lead to maternal death. The purpose of this study was to analyze CT-Value RT-PCR on maternal mortality. This research is an observational analytic study with a cross-sectional approach. The sampling technique used was total sampling. The number of samples were 76 pregnant women with COVID-19 at Abdul Moeloek Regional General Hospital, Lampung Province period March 2020-October 2021. The number of pregnant women who died due to COVID-19 at Abdul Moeloek Hospital, Lampung Province period March 2020-October 2021, was 12 (15.8%) of all pregnant women who were confirmed COVID-19, namely 76 patients. In the statistical test, the p-value was 0.211 (p>0.05), it was concluded that the CT-Value of pregnant women with COVID-19 did not affect maternal mortality. Maternal mortality is not affected by CT-Value PCR pregnant women with confirmed COVID-19.